Differentiation of parenteral anticoagulants in the prevention and treatment of venous thromboembolism - (:unkn) unknown (My University, 2011)
Background: The prevention of venous thromboembolism has been identified as a leading priority in hospital safety. Recommended parenteral anticoagulant agents with different indications for the prevention and treatment of venous thromboembolism include unfractionated heparin, low-molecular-weight heparins and fondaparinux. Prescribing decisions in venous thromboembolism management may seem complex due to the large range of clinical indications and patient types, and the range of anticoagulants available.Methods: MEDLINE and EMBASE databases were searched to identify relevant original articles.Results: Low-molecular-weight heparins have nearly replaced unfractionated heparin as the gold standard antithrombotic agent. Low-molecular-weight heparins currently available in the US are enoxaparin, dalteparin, and tinzaparin. Each low-molecular-weight heparin is a distinct pharmacological entity with different licensed indications and available clinical evidence. Enoxaparin is the only low-molecular-weight heparin that is licensed for both venous thromboembolism prophylaxis and treatment. Enoxaparin also has the largest body of clinical evidence supporting its use across the spectrum of venous thromboembolism management and has been used as the reference standard comparator anticoagulant in trials of new anticoagulants. As well as novel oral anticoagulant agents, biosimilar and/or generic low-molecular-weight heparins are now commercially available. Despite similar anticoagulant properties, studies report differences between the branded and biosimilar and/or generic agents and further clinical studies are required to support the use of biosimilar low-molecular-weight heparins. The newer parenteral anticoagulant, fondaparinux, is now also licensed for venous thromboembolism prophylaxis in surgical patients and the treatment of acute deep-vein thrombosis; clinical experience with this anticoagulant is expanding.Conclusions: Parenteral anticoagulants should be prescribed in accordance with recommended dose regimens for each clinical indication, based on the available clinical evidence for each agent to assure optimal safety and efficacy. © 2011 Fareed et al; licensee BioMed Central Ltd.